Report on the 70th anniversary of Prof. Piotr Franaszek, Kraków, 14 November 2025 - Synowiec, Andrzej (Studia Historiae Oeconomicae, 2025)
On 14 November 2025, the Collegium Novum of the Jagiellonian University hosted the 70th anniversary celebration of the distinguished Polish historian, Prof. Piotr Franaszek, who specialises in economic history, accompanied by the ceremonial presentation of a commemorative book. It was a kind of tribute paid to the honouree by the academic community, in which the professor has been active for almost half a century. The ceremony was attended by numerous guests from the scientific world and his family. The Jagiellonian University Academic Choir added splendour to the speeches and the entire gala.